Transmembrane DomainDependent Functional Oligomerization of Syndecans - Jae Youn Yi; Innoc Han; Eok-Soo Oh (The Scientific World Journal)
Cell surface adhesion receptors of the syndecan family initiate intracellular events through clustering of receptors. This crucial clustering occurs through receptor dimerization or oligomerization, which is mediated by receptor transmembrane domains. However, the exact role of the transmembrane domain during receptor activation is not fully understood. Researchers have not yet determined whether the transmembrane domain functions solely in the physical aspects of receptor clustering, or whether the domain has additional functional roles. Here we review recent advances in understanding the functionality of transmembrane domain–dependent oligomerization of syndecan cell adhesion receptor.